Critical Functions of PP2A-Like Protein Phosphotases in Regulating Meiotic Progression - Lei, Wen-Long; Qian, Wei-Ping; Sun, Qing-Yuan (Frontiers in Cell and Developmental Biology, 2021)
Meiosis is essential to the continuity of life in sexually-reproducing organisms through the formation of haploid gametes. Unlike somatic cells, the germ cells undergo two successive rounds of meiotic divisions after a single cycle of DNA replication, resulting in the decrease in ploidy. In humans, errors in meiotic progression can cause infertility and birth defects. Posttranslational modifications, such as phosphorylation, ubiquitylation and sumoylation have emerged as important regulatory events in meiosis. There are dynamic equilibrium of protein phosphorylation and protein dephosphorylation in meiotic cell cycle process, regulated by a conservative series of protein kinases and protein phosphatases. Among these protein phosphatases, PP2A, PP4, and PP6 constitute the PP2A-like subfamily within the serine/threonine protein phosphatase family. Herein, we review recent discoveries and explore the role of PP2A-like protein phosphatases during meiotic progression.